The dissemination of anthrax from imported wool: Kidderminster 1900–14. Issue 2 (22nd January 2004) - Carter, T
Abstract : Background: A century ago anthrax was a continuing health risk in the town of Kidderminster. The distribution of cases in people and in animals provides an indication of the routes by which spores were disseminated. The response to these cases provides an insight into attitudes to an occupational and environmental risk at the time and can be compared with responses in more recent times. Aims: To assess the distribution of anthrax cases associated with the use of contaminated wool and to review the response to them. Methods: The area studied was Kidderminster, Worcestershire, England, from 1900 to 1914. Data sources were national records of the Factory Inspectorate and local records from the infirmary, Medical Officer of Health and inquest reports, and county agricultural records, supplemented by contemporary and later review articles. Case reports and summary data were analysed, and discussions and actions taken to improve precautions reviewed. Results: There were 36 cases of anthrax, with five deaths, one of which was the sole case of the internal form of the disease. Cases of cutaneous anthrax were most frequently found in those handling raw wool, but they also occurred in workers at later stages of the spinning process and in people with little or no recorded exposure to contaminated wool. Limited precautionary measures were in place at the start of the study period. Some improvements were made, especially in the treatment of infections, but wool with a high risk of anthrax contamination continued to be used and cases continued to arise. Major changes were made to the disposal of waste and to agricultural practice in contaminated areas to curtail outbreaks in farm animals. Conclusions: The introduction of anthrax as a contaminant of imported wool led not only to cases in the highly exposed groups of workers but also to cases in other members of the population and in farm animals. The measures taken during the study period reduced fatalities from cutaneous anthrax but did not eliminate the disease. Public concern about the cases was muted.